ERK3/MAPK6 promotes triple-negative breast cancer progression through collective migration and EMT plasticity - Morazzo, Sofia; Fernandes, Soraia; Fortea, Marina; Skálová, Helena; Pereira-Sousa, Daniel; Cassani, Marco; Vrzalová, Kamila; Kafka, Filip; Vrbský, Jan; Soulez, Mathilde; Meloche, Sylvain; Morten-Seternes, Ole; et al. (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, in which epithelial-to-mesenchymal transition (EMT) plasticity is required for successful metastasis. ERK3 has been implicated in promoting breast cancer migration and invasion, but the mechanisms remain elusive. Here, we investigated ERK3 expression across patient-derived datasets and explored its role in promoting EMT plasticity using different 2D and 3D in vitro models to investigate cell-extracellular matrix adhesion, migration and invasion, anchorage-independent growth, extravasation and colonization. We have established an association between ERK3 overexpression and aggressive breast cancer phenotypes, higher tumour plasticity, as informed by its grade, and poor clinical outcomes. Based on the hypothesis that ERK3 contributes to TNBC progression by supporting a partial-EMT state, we showed that ERK3 contributes to different steps of the metastatic process, especially by enabling collective migration but also by modulating other functional aspects related to an active EMT program. In conclusion, our results demonstrate that ERK3 contributes to TNBC progression and potentially metastasis by promoting EMT plasticity and collective migration.